Multiple inoculations of ductile iron and the effects on properties - Badmos, Adebayo; Fakehinde, Kelvin (International Journal of Engineering and Technology, 2015)
Multiple inoculation of ductile iron and the effects on the structure and mechanical properties have being investigated. Samples of ductile iron were produced with inoculation carried out either once or twice and with different materials as inoculants. Ferrosilicon was used for the primary inoculation and either ferrosilicon or nickel-ferrosilicon for the secondary inoculation. It is observed that the nodules produced are more and finer with multiple inoculations and the effect is more pronounced with nickel-ferrosilicon as the secondary inoculant. Multiple inoculations produce an increase in the hardness of ductile iron when ferrosilicon is used as the secondary inoculant while a decrease in the hardness is observed with nickel-ferrosilicon despite the finer nodules. This is explained by the fact that nickel enhances graphitization in cast iron thereby depleting carbon in the matrix and making the cast iron weaker but with more nodules.